Novel Quinazolinones Active against Multidrug-Resistant Mycobacterium Tuberculosis: Synthesis, Antimicrobial Evaluation, and in Silico Exploration of Penicillin-Binding Protein 1A as a Potential Target - Kerda, Marek; Nawrot, Daria; Šlechta, Petr; Domanský, Miroslav; Askari, Asal; Kamangar, Hanieh; Janďourek, Ondřej; Konečná, Klára; Paterová, Pavla; Hlbočanová, Ingrid; Macháček, Miloslav; Mori, Matteo; et al. (ChemMedChem, 2025)
Quinazolinone derivatives have emerged as promising scaffolds in antimicrobial drug discovery. This work focuses on the design, synthesis, and evaluation of novel quinazolinone-based compounds and predicts their potential to interact with mycobacterial penicillin-binding proteins (PBPs). Relying on established structure-activity relationships of antibacterial quinazolinones, a total of 53 compounds belonging to three different structural types are synthesized and biologically evaluated for antimycobacterial, antibacterial, and antifungal activities. Biological evaluations reveal selective efficacy against Mycobacterium tuberculosis with minimum inhibitory concentrations (MICs) as low as 6.25 μg mL-1 for some derivatives, and this activity is preserved against drug-resistant strains. Molecular docking studies suggest a potential allosteric binding site in mycobacterial PBP 1A (PonA1, UniProt ID: P71707), and subsequential molecular dynamics confirm stable binding with key stabilizing interaction between the carbonyl oxygen of the quinazolinone and either ARG399 or ASP474. These findings suggest quinazolinone derivatives as viable candidates for further development as non-β-lactam PBP inhibitors, addressing the urgent need for new antitubercular therapies.
Keywords: Drug Resistance, Multiple, Bacterial; Antifungal Agents; multidrug‐resistant tuberculosis; chinazolinony; Quinazolinones; Structure-Activity Relationship; mnohočetná bakteriální léková rezistence; Antitubercular Agents; molekulární struktura; Penicillin-Binding Proteins; quinazolinones; Molecular Structure; Microbial Sensitivity Tests; antifungální látky; vztah mezi dávkou a účinkem léčiva; antimycobacterial; Molecular Docking Simulation; antituberkulotika; vztahy mezi strukturou a aktivitou; simulace molekulového dockingu; drug designs; proteiny vázající penicilin; penicillin‐binding proteins; mikrobiální testy citlivosti; computational chemistries; medicinal chemistries; Dose-Response Relationship, Drug; Mycobacterium tuberculosis